TENTANG REALITAS DARI SEGALA SESUATU - Agus Budiyanto (Jurnal Filsafat "WISDOM", 2018)
The focus of the discussion in this article contains an analysis of reality, from the lowest level to the highest, based on physical science, Metamathematics and The Higher Infinite. Incompleteness theorem will play an important role in this discussion. As an application of such analysis, it will be discussed in this article the interpretation of Jalaluddin Rumi’s mystical experience of reality via his poem entitled “A Garden Beyond Paradise”. In this poem, Rumi emphasized that there is a reality that is much higher and greater than paradise, namely the reality of the Godhead. Human should not be satisfied with just paradise, he should continue his spiritual journey to unite with the Godhead.